Letter: sublingual dosing of tacrolimus in transplant patients―interesting concept to overcome first pass effects. Authors' reply. Issue 1 (7th June 2017) - Benítez, C.; Vargas, J. I.; Solari, S.
Abstract : Linked Content This article is linked to Solari et al and Srinivas papers. To view these articles visithttps://doi.org/10.1111/apt.14022 andhttps://doi.org/10.1111/apt.14087 .